A people's history of Christianity : the other side of the story - Bass, Diana Butler, 1959- (New York HarperOne, an imprint of Harper Collins Publishers, 2010)
While bringing to life the movements, personalities, and spiritual disciplines that have always informed and ignited Christian worship and social activism, Butler Bass persuasively argues that corrective--even subversive--beliefs and practices have always been hallmarks of Christianity and are necessary to nourish communities of faith.
The way : early Christianity, 100-500. Christianity as a way of life ; Devotion : the love of God ; Ethics : the love of neighbor -- The cathedral : medieval Christianity, 500-1450. Christianity as spiritual architecture ; Devotion : paradise restored ; Ethics : who is my neighbor? -- The word : Reformation Christianity, 1450-1650. Christianity as living words
"Includes a new reading group guide"--P. [4] of cover.
Includes bibliographical references (p. [315]-341) and index.
Keywords: Church history; Liberalism -- Religious aspects -- Christianity -- History